2020
DOI: 10.1093/cvr/cvaa078
|View full text |Cite|
|
Sign up to set email alerts
|

The ACE2 expression in human heart indicates new potential mechanism of heart injury among patients infected with SARS-CoV-2

Abstract: A new type of pneumonia caused by a novel coronavirus SARS-CoV-2 outbreaks recently in China and spreads into many other countries. This disease, named as COVID-19, is similar to patients infected by SARS-CoV and MERS-CoV, and nearly 20% of patients developed severe condition. Cardiac injury is a prevalent complication of severe patients, exacerbating the disease severity in coronavirus disease 2019 (COVID-19) patients. Angiotensin-converting enzyme 2 (ACE2), the key host cellular receptor of SARS-CoV-2, has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
998
6
56

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,025 publications
(1,147 citation statements)
references
References 7 publications
37
998
6
56
Order By: Relevance
“…Related corona viral infections (SARS and MERS) also had cardiac involvement. Here, we found that expression of the viral receptor ACE2 is higher in pericytes than in CM, as previously reported 87 , but also that neither pericytes nor CM express the protease that prime viral entry, TMPRSS2 . Instead CM and pericytes express CTSB and CTSL , which may also promote viral entry.…”
Section: Discussionsupporting
confidence: 90%
“…Related corona viral infections (SARS and MERS) also had cardiac involvement. Here, we found that expression of the viral receptor ACE2 is higher in pericytes than in CM, as previously reported 87 , but also that neither pericytes nor CM express the protease that prime viral entry, TMPRSS2 . Instead CM and pericytes express CTSB and CTSL , which may also promote viral entry.…”
Section: Discussionsupporting
confidence: 90%
“…Cardiac injury may be ischemia-mediated, and the profound inflammatory and hemodynamic impacts seen in COVID-19 have been hypothesized to cause atherosclerotic plaque rupture or oxygen supply-demand mismatch resulting in ischemia (Madjid et al, 2020). Alternatively, cardiac tissue expresses the ACE2 receptor, further suggesting feasibility of direct viral internalization in cardiomyocytes (Chen et al, 2020). Indeed, case studies have raised suspicion for cardiac injury mediated by direct myocardial viral infection and resulting fulminant myocarditis (Hu et al, 2020;Tavazzi et al, 2020;Zeng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism still remains unclear. Chen et al found that SARS-CoV-2 might attack pericytes of human heart, thus causing capillary endothelial cell dysfunction, leading to cardiovascular disease and cardiac injury [29]. Jin et al suggested that gastrointestinal epithelial cells had a high affinity to ACE2, indicating the potential of fecal-oral transmission and the tendency of gastrointestinal symptoms in dissemination [3].…”
Section: Discussionmentioning
confidence: 99%